Designing Semi-Automated Video Interviews (SAVI): Does Stimulus Format (Video vs. Text) of Instructions and Interview Questions Affect Applicant Perceptions of Social Presence? - Ebrahim, Farheen (School of Management Studies, 2023)
A recent novel development in interview technologies is asynchronous video interviews (AVIs). Although AVIs differ in key design aspects, the effect of AVI design characteristics on applicant reactions is not well understood. The primary purpose of the present study was to determine how differences in AVI stimulus format, such as using either video vs. textual stimuli in instructions and interview questions, may influence applicant perceptions of social presence in interviews. Drawing on social presence theory, it was hypothesised that participants who experienced a video-stimuli based AVI will experience higher levels of social presence than those who experienced a text-stimulus based AVI. Furthermore, given a dearth of previous research on the role of individual differences in AVIs, a secondary purpose of the research was to test the potential moderating role of applicants' social presence preferences and their affinity for technology. To these ends, a pre-registered experiment was used in which participants were randomly assigned into an AVI with either video or text-based instructions and interview questions. Participants in both groups completed a mock digital interview, rated their own levels of perceived social presence, and completed the measures of individual preferences. The experiment was repeated in two independent national samples, including respondents from a South African (N = 58) sample and an American sample (N = 162). The findings revealed mixed results between the two samples. Participants in the SA sample who viewed a video based AVI perceived higher levels of social presence compared to those who viewed a text based AVI, suggesting that AVI stimulus format enhanced applicants' perceptions of social presence. However, these findings did not generalise to the USA sample, where video stimuli did not increase respondents' social presence perceptions. Further analyses showed that the study effects did not depend on applicants' preferences for social presence and their affinity for technology. The study contributes to literature on automated video interview design by showing novel insights into the effects of key design features of digital interviews on applicant reactions. Implications for theory are discussed and recommendations for practice and research are made.